Modes of Translating Culture: Ethnography and Translation - Valero-Garcés, Carmen (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1995)
AbstractThe fields of Translation and Cultural Studies can be seen as encircled within an interdisciplinary framework with fluid boundaries. Focusing my attention on the phrase "the translation of cultures" I will try to explore different meanings of the word "translation'' the way this activity is performed, and by whom. My purpose is to analyze the role of both the ethnographer and the translator as interpreters of experience. I will try to deepen in the dilemmas of "relativism" and "manipulation" of information as a result of that evaluative discrimination they have to do and the current tendencies